Valorization of Lower Grade Resin, Bark, and Fruit of Styrax Sumatrana - Abduh, Muhammad Yusuf; Rahmanita, Ananda Teli; Maulana, Elga Ridho; Nadhira, Valenikhe Fitri; Indira, Tjokorda Istri; Manurung, Robert (International Journal of Innovative Research and Scientific Studies, 2022)
Styrax sumatrana or the kemenyan tree grows in North Sumatera, Indonesia, and its resin is commonly utilized by the local community. Other parts of kemenyan, such as barks and fruits contain valuable compounds that can be extracted to produce high-value bioproducts. This study examined the effect of different resin grades on the physical parameters and cinnamic acid content, delignification pre-treatment period of kemenyan barks with Phanerocahete chrysosporium on the amount of extracted saponin from the barks, and different fruit ripeness on the composition of the fruits. This study showed that grade IV, V and VI resin contain 21.78 to 24.89% cinnamic acid. The isolated cinnamic acid had a purity of 90.9 to 94.3%. Pre-treatments of kemenyan barks were able to degrade 15% of the lignin after 21 days of incubation with Phanerochaete chrysosporium. and increased the amount of extracted saponin up to 7.5-fold higher compared to the non-pre-treated barks. Ripe kemenyan fruits had a higher protein (4.27-10.23%) and crude fat (0.91-7.36%) content as compared to the unripe fruits. Fatty acid composition of the crude fat had been determined and primarily consists of linoleic acid (31.71-42.33%) and palmitic acid (30.44-30.82%) for both ripe and unripe fruits.